2021
DOI: 10.1002/lio2.682
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the current bacteriological profile and antibiotic sensitivity pattern in chronic suppurative otitis media

Abstract: Objective: To determine the current microbiological profile of chronic suppurative otitis media (CSOM), their antimicrobial sensitivity, their resistance pattern to locally available antibiotics and the appropriate antibiotic against isolated microorganisms causing CSOM.Methods: This cross-sectional study involved 91 ear swab specimens obtained from patients clinically diagnosed with active CSOM. Swabs were cultured for microbial identification according to a standard protocol. We performed antibiotic suscepti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 19 publications
3
12
0
Order By: Relevance
“…Another study in Ethiopia reported 56.0% gram-negative bacteria as the predominant species isolated from middle ear discharge, which was consistent with the results of the present study (25). Reports from Somalia, Nigeria and Malaysia agree with the predominance of gram-negative bacteria, with higher frequencies of 77.3%, 71.6% and 75.3%, respectively (32)(33)(34). The reason for the higher prevalence could be the chronic nature of infection, where gram-negative bacteria from external sources gain access to the auditory canal and eventually become predominant.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Another study in Ethiopia reported 56.0% gram-negative bacteria as the predominant species isolated from middle ear discharge, which was consistent with the results of the present study (25). Reports from Somalia, Nigeria and Malaysia agree with the predominance of gram-negative bacteria, with higher frequencies of 77.3%, 71.6% and 75.3%, respectively (32)(33)(34). The reason for the higher prevalence could be the chronic nature of infection, where gram-negative bacteria from external sources gain access to the auditory canal and eventually become predominant.…”
Section: Discussionsupporting
confidence: 91%
“…This study revealed that gramnegative bacterial isolates included E. coli (19.8%), K. pneumoniae (13.2%), Providencia species (10.7%), P. mirabilis (9.1%), P. vulgaris (9.1%), Acinetobacter species (5.0%), Citrobacter species (3.3%) and K. oxytoca (2.5%). Other studies from Ethiopia and other countries have also reported these bacteria at varying frequencies (8,13,18,26,33,43). Variations in climate and geography are possible reasons for the differences in the distribution of bacterial isolates (29).…”
Section: Discussionmentioning
confidence: 90%
“…As a result, a patient-specific combination of ideal drug concentration, dosing frequency, and treatment duration is necessary to achieve the desired antimicrobial effect without the risks of overdosing. A minimum inhibitory concentration (MIC 90 ) of 3.0 μg⸱mL −1 has been identified adequate for CIP to suppress the growth of the most common pathogens isolated from chronic discharging ears, namely the Gram-negative bacterium, P. aeruginosa , and the Gram-positive bacterium, S. aureus [ 11 , 74 ]. However, CSOM patients are typically exposed to significantly higher dosages, with 1 mg per day in topical therapies and 1000 mg per day in systemic therapies [ 61 , 62 ], to compensate for the low drug penetration efficiency [ 75 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, the majority of these reports have indicated a higher occurrence of mono-microbial etiology as opposed to a polymicrobial growth [ 10 ]. Furthermore, the bacteriological analysis of CSOM has identified Staphylococcus aureus ( S. aureus ) and Pseudomonas aeruginosa ( P. aeruginosa ) as the most common pathogens associated with it [ 11 ]. The Gram-positive bacterium, S. aureus , has shown a higher prevalence in pediatric cases of CSOM, while the Gram-negative bacterium, P. aeruginosa has been more frequently isolated in adults [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Out of the 139 samples that had bacterial growth: 93.5% had a growth of single bacteria and 6.5% of participants showed growth of more than one bacterium. Among participants diagnosed to have mucosal and 69.2% of the isolated organisms were monomicrobial, 14.3% were polymicrobial, and only 6.6% were mixed growth of more than three microorganisms [28]. Kombade et al, reported that out of 109 total isolates, monomicrobial growth was seen in 90.8% of samples and 9.2% with polymicrobial growth [27].…”
Section: Discussionmentioning
confidence: 99%